Pertanggungjawaban Korporasi Dalam KUHP Baru - Mulyani, Sri; Soraya, Iga Sonia; Berlianti, Lara; Fikri, Husnul; Hendrison, Hendrison; Andre, Andre (Innovative: Journal Of Social Science Research, 2024)
The new Criminal Code significantly expands the scope of corporate criminal liability in Indonesia. This research analyzes in depth the regulations regarding criminal acts of corruption involving corporations in the new Criminal Code through comparative studies with previous regulations and analysis of jurisprudence. This research identifies challenges and opportunities in law enforcement against criminal acts of corporate corruption. It is hoped that the results of this research can provide more effective policy recommendations in eradicating corruption in the business environment.